A Comparison of DNA Extraction Using AutoMate Express™ and EZ1 Advanced XL from Liquid Blood, Bloodstains, and Semen Stains. Issue 4 (17th May 2013) - Fujii, Koji; Inokuchi, Shota; Kitayama, Tetsushi; Nakahara, Hiroaki; Mizuno, Natsuko; Sekiguchi, Kazumasa
Abstract In this study, DNA was extracted using an AutoMate Express™ and an EZ1 Advanced XL from liquid blood, fresh and aged bloodstains, and fresh and aged semen stains. Extracted DNA was quantified by real‐time PCR using the D17Z1 locus. Short tandem repeat typing was performed using an AmpFℓSTR® Identifiler kit. The yields of DNA obtained by the AutoMate Express™ were higher from fresh bloodstains and fresh semen stains, almost the same from aged bloodstains and aged semen stains, but slightly lower from liquid blood compared with those obtained by the EZ1 Advanced XL. The addition of dithiothreitol or the use of PrepFiler™ lysis buffer improved the EZ1 Advanced XL results from fresh bloodstains, but not for liquid blood and aged bloodstains. Our results demonstrated that the PrepFiler™ lysis buffer is the main contributor to the higher DNA yields of the AutoMate Express™ for fresh bloodstains.